2002
DOI: 10.1002/jmri.10081
|View full text |Cite
|
Sign up to set email alerts
|

Fast imaging of phosphocreatine in the normal human myocardium using a three‐dimensional RARE pulse sequence at 4 Tesla

Abstract: Purpose: To investigate the use of a three-dimensional rapid acquisition with relaxation enhancement (RARE) pulse sequence for direct acquisition of phosphocreatine (PCr) images of the human myocardium. Materials and Methods:A short elliptical birdcage radiofrequency (RF) body coil was constructed to produce a uniform flip angle throughout the chest cavity. In vivo images using a spectrally-selective RARE sequence with a spatial resolution of 1.2 cm ϫ 1.2 cm ϫ 2.5 cm (4 cm 3 ) were acquired in nine minutes and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…A transaxial imaging plane was prescribed through the metatarsal head region of the foot. Separate images of PCr and Pi cellular metabolites were acquired using a rapid acquisition with relaxation enhancement (RARE) pulse sequence with chemical selectivity capabilities (7). The PCr and Pi images were acquired simultaneously in a single 6-min scan.…”
Section: Methodsmentioning
confidence: 99%
“…A transaxial imaging plane was prescribed through the metatarsal head region of the foot. Separate images of PCr and Pi cellular metabolites were acquired using a rapid acquisition with relaxation enhancement (RARE) pulse sequence with chemical selectivity capabilities (7). The PCr and Pi images were acquired simultaneously in a single 6-min scan.…”
Section: Methodsmentioning
confidence: 99%
“…Such techniques, however, are inherently slow and require careful repositioning of the coil for the acquisition of both the anterior and posterior areas of the muscles. Compared to chemical shift imaging, spectrally selective 31 P imaging sequences (22–27) can increase the temporal resolution of the PCr measurement when studying the dynamics of muscle recovery, following a single repetition of the exercise experiment (28, 29). Previously, we have demonstrated that imaging the entire volume of the lower leg is feasible both at 3 and 7 T with significantly improved spatial resolution (4.2 and 1.6 mL, respectively) and temporal resolution of 24 s per three‐dimensional (3D) dataset (30).…”
Section: Introductionmentioning
confidence: 99%
“…Abnormal Pi:PCr ratios have been associated with diseases that affect the muscle tissue of the extremities (2, 3, 5, 7). The rapid acquisition with relaxation enhancement (RARE) (8) pulse sequence allows the acquisition of many spin echoes during each TR period, making it well suited to the imaging of tissues or molecules with long T 1 and T 2 relaxation times such as the myocellular Pi and PCr (912). Methods for creating PCr images using the RARE sequence have been proposed.…”
Section: Inroductionmentioning
confidence: 99%
“…Furthermore, these methods can only be used to acquire images of a single 31 P moiety with each scan. More recently PCr images of the human myocardium and skeletal muscle have been acquired using the RARE sequence with a chemical-shift selective excitation pulse (12). While PCr images of muscle can be used to identify regions of necrosis, they lack the sensitivity of Pi:PCr ratio maps to measure subtle changes that can occur as diseases progress (13, 57).…”
Section: Inroductionmentioning
confidence: 99%